2023
DOI: 10.1093/cid/ciad341
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the Introduction of a Package of Diagnostic Tools, Diagnostic Algorithm, and Training and Communication on Outpatient Acute Fever Case Management at 3 Diverse Sites in Uganda: Results of a Randomized Controlled Trial

Abstract: Background Increasing trends of antimicrobial resistance are observed around the world, driven in part by excessive use of antimicrobials. Limited access to diagnostics, particularly in low- and middle-income countries, contributes to diagnostic uncertainty, which may promote unnecessary antibiotic use. We investigated whether introducing a package of diagnostic tools, clinical algorithm, and training-and-communication messages could safely reduce antibiotic prescribing compared with current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…The reduction of antibiotic prescription associated with the ePOCT+ intervention in our study is consistent with our previous research with CDSAs in Tanzania in more controlled research settings 20 , 21 , 33 . However, the results differ from other studies evaluating CDSAs implemented in routine health programs in Nigeria, Afghanistan, Burkina Faso and South-Africa, and in a controlled study setting in Uganda, which found smaller and even no reduction in antibiotic prescription 22 24 , 34 , 35 . There are a number of differences that may explain the divergent results.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction of antibiotic prescription associated with the ePOCT+ intervention in our study is consistent with our previous research with CDSAs in Tanzania in more controlled research settings 20 , 21 , 33 . However, the results differ from other studies evaluating CDSAs implemented in routine health programs in Nigeria, Afghanistan, Burkina Faso and South-Africa, and in a controlled study setting in Uganda, which found smaller and even no reduction in antibiotic prescription 22 24 , 34 , 35 . There are a number of differences that may explain the divergent results.…”
Section: Discussioncontrasting
confidence: 99%
“…This is particularly true in low-middle–income countries. Studies of malaria RDTs and three recently published randomized controlled trials assessing the impact of implementing a package of diagnostic tools on antimicrobial prescribing are notable exceptions [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%